Hibridisasi Sistem Photovoltaic dan Thermoelectric Generator sebagai Konverter Energi Cahaya dan Termal Surya Menjadi Energi Listrik - Rifky; M. Naufal Fadrurrahman; Thoriq Muhammad Nur Zain; Hafizh Raihan (Prosiding Seminar Nasional Teknoka, 2024)
Solar energy is energy that is classified as new and renewable energy. Utilization of solar radiation energy into clean electrical energy through solar panels. This study uses solar panels that are integrated with thermoelectric modules. This study aims to improve the performance of solar panels that have been hybridized with thermoelectric generators arranged in parallel. The method used in this study is experimental, starting with the design and manufacture of research tools. The research tool is a model of a building whose roof has a slope of 30o and is equipped with a hybrid system consisting of a set of solar panels, a thermoelectric generator, and a cooling system that allows the thermoelectric generator to be cooled. The hybrid device includes two different systems. The first system, a solar panel with a thermoelectric generator, is assembled using a separate rack, so the solar panel with a thermoelectric generator is located on a separate rack. The second system, solar panels and thermoelectric generators are assembled into an integrated circuit on the same rack. The variables measured in this study are the intensity of sunlight, ambient temperature, solar panel temperature (top and bottom), water temperature, wind speed, humidity, thermoelectric generator temperature, open circuit voltage (Voc), maximum voltage, short circuit current (Isc), and maximum current. The research results show that the efficiency of hybridization with a combined rack system has an average of 18.3%, while with a separate rack system the efficiency is lower with an average of 14.7%. Based on this, hybridization using a fused rack system is more efficient than a separate rack system.